1998
DOI: 10.1007/s004320050134
|View full text |Cite
|
Sign up to set email alerts
|

Fotemustine and interferon à2b in metastatic malignant melanoma

Abstract: The efficacy of treatment with fotemustine and interferon (IFN) alpha was evaluated in metastatic melanoma. A group of 50 patients with metastatic malignant melanoma were treated with a combination of IFNalpha2b and the nitrosourea fotemustine. The patients received 10 MU IFN three times weekly for 3 weeks and fotemustine at a dose of 100 mg/m2 on days 8, 15 and 22. After a 5-week rest period, patients with stabilized or responding disease received a maintenance therapy consisting of 10 MU IFN three times a we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Moreover, it has alkylating and carbamoylating effects on nucleic acids (Hayes et al, 1997). Both effects may induce the expression of stress molecules such as hsp70 or MICA which can link chemo-and immunotherapy (Weichenthal et al, 1998). To this end, fotemustine, in combination with sequential immunotherapy for treatment of metastatic ocular melanoma, resulted in a median survival of one year (95% confidence interval 347 and 390 days); the overall survival of patients experiencing an objective benefit of this therapy in the form of an objective response or a stable disease was 19 months.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has alkylating and carbamoylating effects on nucleic acids (Hayes et al, 1997). Both effects may induce the expression of stress molecules such as hsp70 or MICA which can link chemo-and immunotherapy (Weichenthal et al, 1998). To this end, fotemustine, in combination with sequential immunotherapy for treatment of metastatic ocular melanoma, resulted in a median survival of one year (95% confidence interval 347 and 390 days); the overall survival of patients experiencing an objective benefit of this therapy in the form of an objective response or a stable disease was 19 months.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse drug reactions are tolerable except lung toxicity 77 . RRs can also not be improved by combination of temozolomide and cisplatin or fotemustine and INF‐α 78,79 …”
Section: Resultsmentioning
confidence: 99%
“…77 RRs can also not be improved by combination of temozolomide and cisplatin or fotemustine and INF-α . 78,79 In summary, combinations of chemotherapeutic agents have not been proven superior to single-agent monochemotherapy with dacarbazine in randomized trials, and no meaningful effect on survival can be shown by any combination (Evidence level 1a).…”
Section: Polychemotherapiesmentioning
confidence: 99%